NANOSPONGES: A REVIEW - Bhowmik, Himangshu; Venkatesh, D. Nagasamy; Kuila, Anuttam; Kumar, Kammari Harish (International Journal of Applied Pharmaceutics, 2018)
The recent advance in nanotechnology has lead to the development of targeted drug delivery system. However, targeting a molecule to a particular site using a drug delivery system effectively requires a specialized drug delivery system. The discovery of nanosponge has become a significant step in overcoming certain problems such as drug toxicity, poor bioavailability and release of drug in a predictable fashion as they can accommodate both hydrophilic and hydrophobic drug. Nanosponges exhibit a porous structure in nature which has the unique ability to entrap the drug moieties and offers a merit of desire release. Nanosponges are tiny sponges that can circulate in the body to reach the specific site and binds on the surface to release the drug in a controlled and predictable manner. Nanosponges can be formulated by crosslinking of cyclodextrine with carbonyl or di-carboxylate (Crosslinkers). Nano sponge's technology has been explored widely for the delivery of drugs for oral administration, topical administration, and parental administration. Nanosponges can also serve as an effective carrier for enzyme, proteins, vaccine and antibodies. The present review highlights the method of preparation, characterization and their potential application in drug delivery system.